2018
DOI: 10.1016/j.saa.2017.06.045
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, physicochemical and optical properties of bis-thiosemicarbazone functionalized graphene oxide

Abstract: Fluorescent materials are important for low-cost opto-electronic and biomedical sensor devices. In this study we present the synthesis and characterization of graphene modified with bis-thiosemicarbazone (BTS). This new material was characterized using Fourier transform infrared spectroscopy (FT-IR), Ultraviolet-visible (UV-Vis) and Raman spectroscopy techniques. Further evaluation by X-ray diffraction (XRD), thermo-gravimetric analysis (TGA), differential scanning calorimetry (DSC), scanning electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 35 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…Moreover, the hydrophilic nature and electrical properties of GO can be tuned by controlling the amount of oxygen containing functional groups introduced during oxidation of graphite. Due to the aforementioned advantages, GO is investigated for various purposes including photocatalytic and photoelectrochemical hydrogen fuel production from water [1,[9][10][11][12][13][14][15][16], photocatalytic decomposition of organic pollutants [17,18], photocatalytic CO 2 to methanol and formic acid conversion [19][20][21][22][23], photocatalytic disinfection and water purification [24][25][26]. However, pristine GO has some limitations in photoelectrochemical energy conversion efficiency due to its lower electrical conductivity and higher photoelectron-hole charge carrier recombination.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the hydrophilic nature and electrical properties of GO can be tuned by controlling the amount of oxygen containing functional groups introduced during oxidation of graphite. Due to the aforementioned advantages, GO is investigated for various purposes including photocatalytic and photoelectrochemical hydrogen fuel production from water [1,[9][10][11][12][13][14][15][16], photocatalytic decomposition of organic pollutants [17,18], photocatalytic CO 2 to methanol and formic acid conversion [19][20][21][22][23], photocatalytic disinfection and water purification [24][25][26]. However, pristine GO has some limitations in photoelectrochemical energy conversion efficiency due to its lower electrical conductivity and higher photoelectron-hole charge carrier recombination.…”
Section: Introductionmentioning
confidence: 99%
“…31 Chen et al reported edge-modified GO quantum dots by arylamine-based polyazomethine and used as ternary memory devices to improve the memory capacity of binary memory devices. 30 The edgemodified GOs can also be used as DNA biosensors for breast cancer detecting during early diagnosis, 27 fluorescent materials for biomedical sensor and low-cost photoelectric devices, 28 drug delivery for cancer treatment, 29 etc.…”
Section: Introductionmentioning
confidence: 99%
“…When −COOH groups at edges of GO are treated with organic amines or alcohols after activation with thionyl chloride, or using dehydrants like N -hydroxysuccinimide, N , N ′-dicyclohexyl carbodiimide, and N -(3-(dimethylamino)­propyl- N ′-ethylcarbo­diimide) hydrochloride, it will facilitate the formation of ester or acid amide derivatives. Khatri found that octadecylamine edge-modified reduced GO shows friction-reducing property due to the low interfacial shear strength under rolling contact stress . Chen et al.…”
Section: Introductionmentioning
confidence: 99%
“…The fluorescence emission spectra of 5a , 5b , and 5c in ethanol appear to peak at 381, 389, and 420 nm, respectively. The fluorescence spectrum of 5c is red-shifted compared to that of 5a and 5b [15] . Furthermore, the fluorescence emission spectra of 5a, 5b , and 5c were calculated by optimizing the geometries at their respective excited states using the TD-M06/6-311 G⁎⁎ method and are shown in Fig.…”
Section: Resultsmentioning
confidence: 87%